Economic Renewal and Demographic Change Evaluation of policies for well functioning local labour markets in the Nordic countries - Elli Heikkilä,; Mats Johansson; Ingi Runar Edvardsson; Torben Dall Schmidt; Lasse Sigbjørn Stambøl; Lars Olof Persson (European Regional Science Association (ERSA), 2004)
Regional imbalances caused by and effecting demographic change are unevenly spread between the Nordic countries. A common threat is that of labour shortage, which is already experienced in certain sectors in particular regions and forecasted on a broader scale in the future. The also common characteristic of an ageing labour force has important side effects from a social and economic perspective in some of the countries and regions, e g increasing rates of sickness leave. The sustainability in economic and social terms of several labour markets is challenged as population decline continues. The institutional preconditions for addressing these and other problems related to economic renewal and demographic change are basically quite similar in all Nordic countries, yet differ in a number of important details. The purpose of this paper is to analyse and evaluate how the different portfolios of policy instruments in Denmark, Sweden, Iceland, Norway and Finland are reflected in differing performance of local labour markets with similar economic and demographic structure and size. A leading hypothesis is that policies reducing risks for the individual when moving between different labour market statuses promotes the flexibility of labour markets. The empirical analysis is based on the transitional characteristics of the local labour market. Each transition or career - such as those from school to job and vice versa, from parental or sick leave to job, from unemployment to job, etc - can be temporary and repetitious. There are a number of theories explaining this increasingly transitional labour force behaviour stressing the individual choice of life-style, and life chances or careers perceived in different places. There are also theories stressing the importance of social capital. Supply side oriented labour market policy is adapting to the differing ”tastes” of individuals and life-style groups. Transition itself is also enforced by policy intervention to encourage temporary leave for life-long learning periods and parental leave. This transition can thus be viewed as a supplementary dimension to that usually described as labour mobility, i.e. qualification or de-qualification careers, inter-industry mobility and inter-regional or international migration.
Keywords: 330